The Indian-Chinese confrontation in the Himalayas: A stress test for India's strategic autonomy - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2020)
The confrontation between Indian and Chinese troops in the Himalayas, which has been ongoing since the beginning of May, has escalated into the most serious crisis in relations between the two countries in 45 years. On 15 June, for the first time since 1975, 20 Indian and an unknown number of Chinese soldiers were killed in an incident. The current crisis, unlike previous ones, has wider territorial and political dimensions. It shakes the previous border regime and strains the relationship of trust that was laboriously built up between Prime Minister Narendra Modi and President Xi Jinping. The confrontation is also a test of India's strategic autonomy. This cornerstone of Indian foreign policy also includes the claim to an independent role in the geostrategic tensions between China and the United States in the Indo-Pacific.
Keywords: 320